Kernaspekte van ’n model vir skoolsukses in arm gemeenskappe - Kamper, G. D. (Koers, 2006)
Key aspects of a model for school success in poor communities Some schools in impoverished communities are effective and successful in the face of the most difficult socio-economic circumstances and challenges. This phenomenon was investigated in a research project which had three phases. The first entailed a literature survey, culminating in a taxonomy of determinants of school success. The second phase consisted of the application of the taxonomy in field work in selected successful schools in impoverished communities. The third phase comprised interpretation of theoretical and empirical data, culminating in a model which depicts partnership as the central factor in all values and mechanisms pertaining to a successful school in an impoverished community. The model’s potential value is indicated, inter alia in guiding schools in impoverished communities towards meaningful self-assessment and change.